Acute poisoning with acetamiprid, a type of neonicotinoid insecticide causing severe lactic acidosis: A case report - Mohanaruban Pravinson (SAGE Publishing, 2021)
Acetamiprid is a type of neonicotinoid that belongs to the new class of insecticides. It is fatally toxic to insects by acting as an agonist to nicotinic acetylcholine receptors. Cases with neonicotinoids including acetamiprid poisoning in humans were reported around the world. Only one case with acetamiprid poisoning associated with severe adverse effects has been described from Sri Lanka. Serious side effects will occur if it is consumed in excess amount. Here, we described a case of acetamiprid poisoning in a man who developed severe lactic acidosis, myocardial suppression, hyperglycemia, and intestinal obstruction following accidental intake of acetamiprid insecticide. The patient was managed conservatively as there is no specific management mentioned in the literature.